Entrustable professional activities in nursing education: a scoping review - Jan Kottner; Asja Maaz; Jonas Pietsch (BMJ Open)
Objectives Entrustable professional activities (EPAs) have been used in undergraduate and graduate medical education and in other health professions for a long time. They are regarded as a suitable way for bridging the gap between competency-based education and actual work tasks in the workplace. In nursing education, EPA development started later, and it is unclear which EPAs have been developed and implemented yet. This scoping review aims to identify which EPAs have been developed in nursing education, which of these have even been implemented and what the empirical evidence supports any effects of implementation.Design Scoping review using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews.Data sources MEDLINE and EMBASE via OVID, CINAHL and ERIC via EBSCOhost were searched for the period 1 January 1995 to 31 December 2023.Eligibility criteria Publication period from the first mention of EPAs in 1995 to 2023, no language restrictions, all types of literature if they had a clear mention of EPAs, all academic nursing education fields, EPAs had to be mentioned in the title or abstract.Data extraction and synthesis Screening was conducted in a two-stage process with two authors. 13 suitable articles were included which describe either the development, implementation or assessment of EPAs.Results Results indicated that EPAs have been developed in 16 areas of nursing education, including special areas such as palliative care or emergency/intensive care. The activities health status assessment, care measures, leadership/management, diagnoses, care plans and protocols, emergency care measures and participation in diagnostics and/or therapy were described most often. In 4 out of 13 cases, EPAs were implemented. Described evidence indicated that the use of EPAs improved critical thinking, promoted flexibility in teaching and led to a mindset change.Conclusions EPAs are increasingly developed and implemented in nursing education. There seem to be overlaps between EPAs mainly covering the steps of the nursing care process.